4-1BB/CD137 triggering on human monocytes leads to differentiation into macrophages with increased metabolic support and tumoricidal capacity - Stoll, Andrej; Bruns, Heiko; Gamali, S.; Saul, Domenica; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Accumulation of T-cell-suppressive PD-L1 high extracellular vesicles is associated with GvHD and might impact GvL efficacy - Baur, Rebecca; Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Völkl, Simon; Gießl, Andreas; Flamann, Cindy; Bruns, Heiko; Schlötzer-Schrehardt, Ursula; Böttcher, Martin; Schewe, Denis M.; Fischer, Thomas; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for a number of hemato-oncological disorders. In fact, allo-HSCT is considered as one of the most successful immunotherapies as its clinical efficacy is based on the donor T-cells' capacity to control residual disease. This process is known as the graft-versus-leukemia (GvL) reaction. However, alloreactive T-cells can also recognize the host as foreign and trigger a systemic potentially life-threatening inflammatory disorder termed graft-versus-host disease (GvHD). A better understanding of the underlying mechanisms that lead to GvHD or disease relapse could help us to improve efficacy and safety of allo-HSCT. In recent years, extracellular vesicles (EVs) have emerged as critical components of intercellular crosstalk. Cancer-associated EVs that express the immune checkpoint molecule programmed death-ligand 1 (PD-L1) can suppress T-cell responses and thus contribute to immune escape. At the same time, it has been observed that inflammation triggers PD-L1 expression as part of a negative feedback network. Here, we investigated whether circulating EVs following allo-HSCT express PD-L1 and tested their efficacy to suppress the ability of (autologous) T-cells to effectively target AML blasts. Finally, we assessed the link between PD-L1 levels on EVs to (T-)cell reconstitution, GvHD, and disease relapse. We were able to detect PD-L1 + EVs that reached a peak PD-L1 expression at 6 weeks post allo-HSCT. Development of acute GvHD was linked to the emergence of PD-L1 high EVs following allo-HSCT. Moreover, PD-L1 levels correlated positively with GvHD grade and declined (only) on successful therapeutic intervention. T-cell-inhibitory capacity was higher in PD-L1 high EVs as compared with their PD-L1 low counterparts and could be antagonized using PD-L1/PD-1 blocking antibodies. Abundance of T-cell-suppressive PD-L1 high EVs appears to also impact GvL efficacy as patients were at higher risk for relapse. Finally, patients of PD-L1 high cohort displayed a reduced overall survival.Taken together, we show that PD-L1-expressing EVs are present following allo-HSCT. PD-L1 levels on EVs correlate with their ability to suppress T-cells and the occurrence of GvHD. The latter observation may indicate a negative feedback mechanism to control inflammatory (GvHD) activity. This intrinsic immunosuppression could subsequently promote disease relapse.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Immune Evation; T-Lymphocytes; Transplantation Immunology

CD137 (4-1BB) stimulation leads to metabolic and functional reprogramming of human monocytes/macrophages enhancing their tumoricidal activity - Stoll, Andrej; Bruns, Heiko; Fuchs, Maximilian; Nimmerjahn, Falk; Kunz, Meik; Peipp, M.; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (Leukemia, 2021)
Immunotherapies have heralded a new era in the cancer treatment. In addition to checkpoint inhibitors, agonistic antibodies against co-stimulatory immune receptors hold the potential to invoke efficient antitumor immunity. Targeting CD137 has gained momentum based on its ability to drive NK- and T-cell-based responses. CD137-engaging mAbs have already entered clinical trials for different types of tumors showing promising results. Despite the efforts to translate CD137-mediated immunotherapy into clinical practice, little remains known regarding the role of CD137 in human monocytes/macrophages. We found CD137 being expressed on monocytes of healthy controls and at even higher levels in patients with multiple myeloma or CLL. CD137HI(GH) monocytes displayed a distinct phenotypic, transcriptomic, and metabolic profile. They possessed an increased phagocytic capacity enabling superior antibody-dependent phagocytosis (ADPC) of multiple myeloma and lymphoma cells that were treated with anti-CD38 or anti-CD20 mAbs. Triggering CD137 promoted both metabolic and tumoricidal activity in an extracellular signal-regulated kinase (ERK)-dependent fashion. In addition, we observed a phenotypic, transcriptomic, and functional skewing towards a M1-like phenotype. Overall, we introduce CD137 as a positive immune checkpoint on human monocytes/macrophages, which can have therapeutic implications especially in view of synergistic effects when combining CD137 agonists with tumor-targeting antibodies.
CRIS-Team Scopus Importer:2021-06-04

CD137 (4-1BB) triggering leads to metabolic and functional reprogramming of human monocytes/macrophages enhancing their tumoricidal activity - Stoll, Andrej; Bruns, Heiko; Gamali, S.; Saul, Domenica; Fuchs, Maximilian; Nimmerjahn, Falk; Kunz, Meik; Peipp, M.; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Human monocytes display different levels of CD137/4-1BB expression linked to certain immunometabolic features - Stoll, Andrej; Bruns, Heiko; Saul, Domenica; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Identification of HLA-C restricted, HIV-1-specific CTL epitopes by peptide induced upregulation of HLA-C expression - Stoll, Andrej; Bergmann, Silke; Mummert, Christiane; Mueller-Schmucker, Sandra M.; Spriewald, Bernd M.; Harrer, Ellen G.; Harrer, Thomas (Journal of Immunological Methods, 2015)
HIV-1 negative regulatory factor (Nef) can inhibit CTL recognition by downregulation of HLA-A and HLA-B on the cell surface. In contrast, HLA-C is not affected by Nef and a growing number of studies demonstrate an important role of HLA-C for the control of HIV-1. So far, only a limited number of HLA-C restricted CTL epitopes are known. As the mapping of new CTL epitopes is time and labor intensive, we investigated a novel method for the identification of HLA-C restricted CTL epitopes. B-lymphoblastoid cell lines (B-LCLs) and T2-cells were incubated with HIV-1 specific peptides and subsequently stained for HLA-C surface expression using the HLA-C specific antibody DT9. Peptides that led to increased HLA-C surface expression were used for stimulation of PBMC from HIV-1-infected patients. Subsequently, outgrowing cells were tested for peptide recognition in IFN-? ELISPOT assays and HLA restriction of the recognized peptides was analyzed in ELISPOT assays using HLA-matched B-LCL. We observed that known HLA-C binding peptides increase HLA-C surface expression on T2-cells and on HLA-C*0102 and HLA-C*0702 homozygous B-LCL. Moreover, screening of HIV-1 Nef with overlapping peptides for potential C*0702 restricted epitopes using this method revealed a total of 8 peptides which considerably increased cell surface expression of HLA-C. By epitope mapping and functional analysis of peptide-stimulated T-cell lines we were able to define the peptide YPLTFGWCY as a new C*0702-restricted CTL epitope. These results show that the analysis of peptide induced HLA-C upregulation on B-LCL and T2-cells enables the efficient identification of new HLA-C restricted CTL epitopes.
EVALuna2:13104

IL-21 modulates memory and exhaustion phenotype of T-cells in a fatty acid oxidation-dependent manner - Loschinski, Romy; Böttcher, Martin; Stoll, Andrej; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios (Oncotarget, 2018)
T-cell-based therapies represent a promising strategy for cancer treatment. In this context, cytokines are discussed as a bona fide instrument for fine-tuning T- cell biology. One promising candidate is the pleiotropic interleukin-21 (IL-21) with only little being known regarding its direct effects on human T-cells. Thus, we sought out to characterize the impact of IL-21 on T-cell metabolism, fitness, and differentiation. Culturing T-cells in presence of IL-21 elicited a metabolic skewing away from aerobic glycolysis towards fatty acid oxidation (FAO). These changes of the metabolic framework were paralleled by increased mitochondrial fitness and biogenesis. However, oxidative stress levels were not increased but rather decreased. Furthermore, elevated FAO and mitochondrial biomass together with enhanced antioxidative properties are linked to formation of longer lasting memory responses and less PD-1 expression. We similarly observed an IL-21-triggered induction of central memory-like T-cells and reduced levels of PD-1 on the cell surface. Taken together, IL-21 shifts T-cells towards an immunometabolic phenotype that has been associated with increased survivability and enhanced anti-tumor efficacy. In addition, our data reveals a novel interconnection between fatty acid metabolism and immune function regulated by IL 21.
EVALuna2:34164

Immunometabolic alteration in NK cells from multiple myeloma patients - Jacobs, Benedikt; Richter, S.; Stoll, Andrej; Völkl, Simon; Mackensen, Andreas; Mougiakakos, D. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Böttcher-Loschinski, Romy; Böttcher, Martin; Jacobs, Benedikt; Jitschin, Regina; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Leukemia, 2020)
CRIS-Team Scopus Importer:2020-07-31

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Gamali, S.; Böttcher-Loschinski, Romy; Böttcher, Martin; Baur, Rebecca; Jacobs, Benedikt; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Increased PD-1 Expression on Circulating T Cells Correlates with Inferior Outcome after Autologous Stem Cell Transplantation - Richter, Silja; Böttcher, Martin; Stoll, Andrej; Zeremski, Vanja; Völkl, Simon; Mackensen, Andreas; Ekici, Arif Bülent; Jacobs, Benedikt; Mougiakakos, Dimitrios (Transplantation and Cellular Therapy, 2024)
High-dose chemotherapy followed by autologous stem cell transplantation (auto-SCT) is a well-established treatment option for multiple myeloma and malignant lymphoma patients. It is able to induce long-term progression-free survival (PFS) in both patient groups and even provide a cure in patients with aggressive lymphoma. However, relapse is common and has been associated with the pace and quality of immunologic reconstitution after transplantation, as well as with immune cell exhaustion and immunometabolic defects. We aimed to analyze the dynamics of the prototypical exhaustion marker PD-1 on immune cells during reconstitution on high-dose chemotherapy followed by auto-SCT and its impact on PFS. We performed a comprehensive analysis of exhaustion and metabolic markers on immune cells from myeloma and lymphoma patients undergoing auto-SCT using flow cytometry and NanoString technologies. The expression levels of PD-1 were increased during early reconstitution after transplantation on T cells and natural killer (NK) cells, as well as on monocytes. However, while PD-1 expression in NK cells and monocytes normalized over time, PD-1 expression on T cells demonstrated a variable course. Of note, lymphoma patients with continuously increasing PD-1 expression on T cells after auto-SCT had an inferior median PFS of only 146 days, whereas the median PFS was not reached in the lymphoma patients without such a PD-1 expression pattern. T cells from patients with increased PD-1 expression after auto-SCT exhibited an immunometabolic (over)activation and exhausted phenotype compared to T cells from patients with a low PD-1 expression after transplantation, including higher levels of the glycolytic pacemaker enzyme hexokinase 2 and the inhibitory receptor CTLA-4. In addition, proliferating Ki-67+ T cells were more abundant in patients with high PD-1 expression on T cells compared to those with low expression after auto-SCT (11.9% versus 4.2%). PD-1 expression on T cells might serve as an adverse biomarker for lymphoma patients undergoing auto-SCT; however, further validation by larger prospective studies is required.
CRIS-Team Scopus Importer:2024-04-12
Keywords: auto-SCT; exhaustion; PD-1; T cells

Linking Immunoevasion and Metabolic Reprogramming in B-Cell–Derived Lymphomas - Böttcher, Martin; Stoll, Andrej; Mackensen, Andreas; Mougiakakos, Dimitrios; Baur, Rebecca (Frontiers in Oncology, 2020)
Lymphomas represent a diverse group of malignancies that emerge from lymphocytes. Despite improvements in diagnosis and treatment of lymphomas of B-cell origin, relapsed and refractory disease represents an unmet clinical need. Therefore, it is of utmost importance to better understand the lymphomas’ intrinsic features as well as the interactions with their cellular microenvironment for developing novel therapeutic strategies. In fact, the role of immune-based approaches is steadily increasing and involves amongst others the use of monoclonal antibodies against tumor antigens, inhibitors of immunological checkpoints, and even genetically modified T-cells. Metabolic reprogramming and immune escape both represent well established cancer hallmarks. Tumor metabolism as introduced by Otto Warburg in the early 20th century promotes survival, proliferation, and therapeutic resistance. Simultaneously, malignant cells employ a plethora of mechanisms to evade immune surveillance. Increasing evidence suggests that metabolic reprogramming does not only confer cell intrinsic growth and survival advantages to tumor cells but also impacts local as well as systemic anti-tumor immunity. Tumor and immune cells compete over nutrients such as carbohydrates or amino acids that are critical for the immune cell function. Moreover, skewed metabolic pathways in malignant cells can result in abundant production and release of bioactive metabolites such as lactic acid, kynurenine or reactive oxygen species (ROS) that affect immune cell fitness and function. This “metabolic re-modeling” of the tumor microenvironment shifts anti-tumor immune reactivity toward tolerance. Here, we will review molecular events leading to metabolic alterations in B-cell lymphomas and their impact on anti-tumor immunity.
CRIS-Team Scopus Importer:2020-11-27
Keywords: B-cell-derived Non-Hodgkin lymphoma; chronic lymphocytic leukemia; immune escape; immune therapeutics; metabolism

Monitoring of the immunometabolic profile of reconstituting leukocytes upon autologous peripheral blood stem cell transplantation - Richter, Swetlana; Jacobs, Benedikt; Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Oxidative DNA damage in reconstituting T cells is associated with relapse and inferior survival after allo-SCT - Karl, Franziska; Liang, C.; Böttcher-Loschinski, R.; Stoll, Andrej; Flamann, Cindy; Richter, Silja; Lischer, Christopher; Völkl, Simon; Jacobs, Benedikt; Böttcher, M.; Jitschin, R.; Bruns, Heiko; et al. (Blood, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-SCT) is the only curative treatment option for a number of hematologic malignancies. Its therapeutic potential relies on the potency of donor T cells to eliminate residual malignant cells, the so-called graft-versus-leukemia (GVL) effect. Disease relapse remains the most frequent treatment failure and is associated with poor outcome. Therefore, it is inevitable to decipher mechanisms that weaken GVL. In recent years, studies of tumor biology have revealed that metabolic remodeling of the micromilieu can critically regulate immune responses. Accumulation of reactive oxygen species leads to a metabolic condition known as oxidative stress, which can severely hamper T cells. Currently, only a few studies, mainly using preclinical models, have demonstrated the occurrence of oxidative stress after allo-SCTs. Therefore, we sought to investigate oxidative stress in a well-characterized group of patients who underwent allo-SCT and its impact on reconstituting T cells. We identified high concentrations of serum 8-hydroxydeoxyguanosine (8-OHdG) as an established biomarker for oxidative stress. 8-OHdG is one of the major products of DNA oxidation, which is normally rapidly removed. After allo-SCT, T cells accumulated oxidative DNA damage. High cellular 8-OHdG content (8-OHdGhi) was associated not only with signs of enhanced T-cell activation but also premature exhaustion. The inability of 8-OHdGhi T cells to efficiently target malignant cells or produce cytotoxic granzyme B and interferon gamma was associated with a significantly increased relapse risk and a shorter overall survival. Taken together, our novel findings could give reason to focus on bolstering DNA repair in reconstituting T cells as a means to improve GVL efficacy.
CRIS-Team Scopus Importer:2023-03-31

Oxidative stress upon allogeneic hematopoietic stem cell transplantation and its impact on the reconstituting immune system - Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Profiling extracellular vesicles (EV) in patients with acute GvHD after allogeneic stem cell transplantation - Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Rösler, Wolf; Winkler, Julia; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

The IKZF1–IRF4/IRF5 axis controls polarization of myeloma-associated macrophages - Mougiakakos, Dimitrios; Bach, Christian; Böttcher, Martin; Beier, Fabian; Röhner, Linda; Stoll, Andrej; Rehli, Michael; Gebhard, Claudia; Lischer, Christopher; Eberhardt, Martin; Vera, Julio; Büttner-Herold, Maike; et al. (Cancer Immunology Research, 2021)
The bone marrow niche has a pivotal role in progression, survival, and drug resistance of multiple myeloma cells. Therefore, it is important to develop means for targeting the multiple myeloma bone marrow microenvironment. Myeloma-associated macrophages (MAM) in the bone marrow niche are M2 like. They provide nurturing signals to multiple myeloma cells and promote immune escape. Reprogramming M2-like macrophages toward a tumoricidal M1 phenotype represents an intriguing therapeutic strategy. This is especially interesting in view of the successful use of mAbs against multiple myeloma cells, as these therapies hold the potential to trigger macrophage-mediated phagocytosis and cytotoxicity. In this study, we observed that MAMs derived from patients treated with the immunomodulatory drug (IMiD) lenalidomide skewed phenotypically and functionally toward an M1 phenotype. Lenalidomide is known to exert its beneficial effects by modulating the CRBN-CRL4 E3 ligase to ubiquitinate and degrade the transcription factor IKAROS family zinc finger 1 (IKZF1). In M2-like MAMs, we observed enhanced IKZF1 levels that vanished through treatment with lenalidomide, yielding MAMs with a bioenergetic profile, T-cell stimulatory properties, and loss of tumor-promoting capabilities that resemble M1 cells. We also provide evidence that IMiDs interfere epigenetically, via degradation of IKZF1, with IFN regulatory factors 4 and 5, which in turn alters the balance of M1/M2 polarization. We validated our observations in vivo using the CrbnI391V mouse model that recapitulates the IMiD-triggered IKZF1 degradation. These data show a role for IKZF1 in macrophage polarization and can provide explanations for the clinical benefits observed when combining IMiDs with therapeutic antibodies. See related Spotlight on p. 254
CRIS-Team Scopus Importer:2021-03-19

The Oncometabolite 5′-Deoxy-5′-Methylthioadenosine Blocks Multiple Signaling Pathways of NK Cell Activation - Jacobs, Benedikt; Schlögl, Sebastian; Strobl, Carolin; Stoll, Andrej; Mougiakakos, Dimitrios; Malmberg, Karl Johan; Mackensen, Andreas; Aigner, Michael; Völkl, Simon (Frontiers in Immunology, 2020)
Tumor cells develop various mechanisms to escape immune surveillance. In this context, oncometabolites secreted by tumor cells due to deregulated metabolic pathways, have been in the spotlight of researchers during the last years. 5′-Deoxy-5′-methylthioadenosine (MTA) phosphorylase (MTAP) deficiency in tumors results in the accumulation of MTA within the tumor microenvironment and thereby negatively influencing immune functions of various immune cells, including T and NK cells. The influence of MTA on T cell activation has been recently described in more detail, while its impact on NK cells is still largely unknown. Therefore, we aimed to illuminate the molecular mechanism of MTA-induced NK cell dysfunction. NK cell cytotoxicity against target cells was reduced in the presence of MTA in a dose-dependent manner, while NK cell viability remained unaffected. Furthermore, we revealed that MTA blocks NK cell degranulation and cytokine production upon target cell engagement as well as upon antibody stimulation. Interestingly, the immune-suppressive effect of MTA was less pronounced in healthy donors harboring an expansion of NKG2C+ NK cells. Finally, we demonstrated that MTA interferes with various signaling pathways downstream of the CD16 receptor upon NK cell activation, including the PI3K/AKT/S6, MAPK/ERK, and NF-κB pathways. In summary, we revealed that MTA blocks NK cell functions like cytotoxicity and cytokine production by interfering with the signaling cascade of activating NK cell receptors. Specific targeting of MTA metabolism in MTAP-deficient tumors therefore could offer a promising new strategy to reverse immune dysfunction of NK cells within the tumor microenvironment.
CRIS-Team Scopus Importer:2020-10-30
Keywords: 5′-deoxy-5′-methylthioadenosine; CD16 signaling; NK cells; NKG2C; tumor escape mechanism

Thrombopoietin receptor agonists for acquired thrombocytopenia following anti-CD19 CAR-T-cell therapy: A case report - Jitschin, Regina; Kharboutli, Soraya; Stoll, Andrej; Büttner-Herold, Maike; Schmidt, Daniela; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Journal for ImmunoTherapy of Cancer, 2021)
Chimeric antigen receptor (CAR)-modified T-cells targeting CD19 represent a promising therapy for relapsed or refractory (r/r) lymphoma and leukemia. The most common adverse events are immune related and include cytokine release syndrome and neurotoxicity. However, early and late hematological toxicity has emerged as a substantial clinical hurdle leading among others to an increased risk for infections or bleeding. The underlying pathophysiology remains elusive and supportive measures comprise stem cell support or the use of growth factors. Here, we report a 66-year-old woman with r/r diffuse large B-cell lymphoma that received anti-CD19 CAR-T-cells achieving a complete metabolic remission. At month 3 after adoptive cell transfer, the patient still exhibited a grade 3 anemia and a grade 4 thrombocytopenia. The latter required regular platelet transfusions. Bone marrow smear revealed hypocellularity without dysplasia. Despite reduced megakaryopoiesis, immature platelet fraction was elevated indicating an at least partially consumptive underlying component. Based on the successful use of Romiplostim, a thrombopoietin receptor-agonist, in aplastic anemia and immune thrombocytopenia, we treated our patient accordingly. Platelet count (and hemoglobin levels) increased and the patient remains transfusion-free. Taken together, our therapeutic approach could represent a novel strategy for managing CAR-T-cell-related hematotoxicity but, self-evidently, requires further controlled clinical studies.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; chimeric antigen; hematologic neoplasms; immunotherapy; receptors